The Contribution of Authentic Leadership, Work Motivation, Work Ethic, and Academic Supervision To Teachers Organizational Commitment at SMP Negeri 2 Kuta Utara - Ni Putu Ayu Novia Dewi; Anak Agung Gede Agung; Kadek Rihendra Dantes (Pelopor Publikasi Akademika, 2025)
This research aims to analyze the contribution of authentic leadership, work motivation, work ethic and academic supervision towards organizational commitment of teachers at SMP Negeri 2 Kuta Utara. The research data is analyzed using descriptive statistical analysis techniques, inferential statistics, product moment correlation tests, partial correlations, and multiple correlations/regressions, which is analyzed using IBM SPSS Statistics 26. The results of the research show that there are (1) there is a significant contribution of authentic leadership to the organizational commitment of teachers, with a correlation coefficient (r1y) of 0.674, a partial correlation coefficient of 0.310, and an effective contribution of 11.80%, (2) there is a significant contribution of work motivation to the organizational commitment of teachers, with a correlation coefficient (r2y) of 0.827, a partial correlation coefficient of 0.310, and an effective contribution of 24.56%, (3) there is a significant contribution of work ethic to the organizational commitment of teachers, with a correlation coefficient (r3y) of 0.865, a partial correlation coefficient of 0.273, and an effective contribution of 25.60%, (4) there is a significant contribution of academic supervision to the organizational commitment of teachers, with a correlation coefficient (R4y) of 0.757, a partial correlation coefficient of 0.410 and an effective contribution of 21.35%, (5) there is a significant contribution of authentic leadership, work motivation, work ethic and academic supervision together to the organizational commitment of teachers with a correlation coefficient (Ry.1,2,3,4) of 0.912 and an effective contribution of 83.31%.